RETRACTED: Dampak Pembangunan di Era Globalisasi terhadap Perwujudan Hak Asasi Manusia di Lingkungan yang Baik dan Sehat - Muhammad Prasetya; Adyuta Camara Paris (Jurnal Hukum Lex Generalis, 2022)
The manuscript entitled "The Impact Of Development In The Era Of Globalization On The Realization Of Human Rights In A Good And Healthy Environment" published in Lex Generalis Law Journal Vol.3 No.12 (December 2022) on the link https://ojs.rewangrencang.com/index.php/JHLG/article/view/317 to the Editor's search has the main similarity substance with the manuscript that has been published previously in another journal, namely Jurnal Pembangunan Hukum Vol.1 No.3 (2014) on the http://jurnal.unissula.ac.id/index.php/PH/article/view/1487/1155. Based on that finding, the editorial decide to retract this manuscript. The announcement of the retraction of this manuscript can be accessed via the following link: https://ojs.rewangrencang.com/index.php/JHLG/article/view/366.